Mid-term radiological and functional results of biological reconstructions of extremity-located bone sarcomas in children and young adults - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Biological reconstruction is a useful option for reconstruction following bone sarcoma resection in children. The mid-term functional and radiological outcomes of biological reconstructions after resection of bone sarcomas in children are presented in this study. Eighteen patients [average age 12.5 years (range 4-22 years)] with primary sarcomas of long bones underwent wide surgical resection and biological reconstruction. The bone defects were managed by intercalary (n=14), osteoarticular (n=3) reconstructions and arthrodesis (n=1) with a vascularized fibular graft (VFG). VFG was combined with a massive allograft in seven lower extremity reconstructions. The average follow-up was 45.7 months (range 25-78 months). Graft union and graft hypertrophy was observed in 17 (94.4%) of 18 patients at 12 months. The VFG-allograft osteointegration rate was 100% at 24 months. The average final follow-up Musculoskeletal Tumor Society (MSTS) scores for lower and upper extremity reconstructions were 79.7% (range 66.6-90%) and 80.9% (range 53.3-100%), respectively. Four (22.2%) complications, including nonunion (n=1), implant failure (n=1), infection (n=1) and skin necrosis (n=1), required reoperation. The disease relapsed in three (16.6%) patients. Defect size and VFG length did not correlate with MSTS scores and radiological parameters (P>0.05). Biological reconstruction with VFG can provide permanent stability and progressively increasing functional and radiological results. Copyright (C) 2015 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: biological reconstruction; vascularized fibular autograft; bone sarcoma; VASCULARIZED FIBULAR GRAFTS; LIMB-SALVAGE; TUMOR RESECTION; ENDOPROSTHETIC REPLACEMENT; EXTRACORPOREAL IRRADIATION; LIQUID-NITROGEN; PROXIMAL TIBIA; ALLOGRAFTS; DEFECTS; REIMPLANTATION